Dispositional accounts of abilities*. Issue 8 (August 2017) - Vetter, Barbara; Jaster, Romy
Abstract: This paper explores the prospects for dispositional accounts of abilities. According to so‐called new dispositionalists, an agent has the ability to Φ iff they have a disposition to Φ when trying (or being otherwise properly motivated) to Φ . We show that the new dispositionalism is beset by some problems that also beset its predecessor, the conditional analysis of abilities, and bring up some further problems. We then turn to a different approach, which links abilities not to motivational states but to the notion of success, and consider ways of implementing that approach. Our results suggest that there are principled disanalogies between abilities and disposition which prevent any dispositional account of abilities from succeeding.